Девятый конвой - Тамоников Александр Александрович (Лучшие романы о войне, 2018)
Экземпляры: ф.15 (20180906) / Инвентарный номер: 50445 / Цена: 107.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Т 17 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44